Towards automatic Maude specifications generation from C functions - fateh boutekkouk (Journal of Innovation Information Technology and Application (JINITA), 2023)
In this paper, we aim to contribute to the knowledge about how imperative C functions can be transformed to Maude functional and system modules respectively. Maude is a formal specification language characterized by simplicity, expressivity and good performance. It is a multi-paradigm meta-language based on rewriting logic and equational theories used to specify, simulate and formally verify concurrent and distributed systems. Maude has been used to define the operational semantics of many programming and specification languages. In particular, the addition of this paper is to close the gap between a subset of the C standard language and Maude relying on a transformational approach.